Pengaruh Strategi Promosi Dan Social Media Melalui Electronic Word Of Mouth Terhadap Keputusan Berkunjung Pada Wisata Edukasi Dadaprejo Kota Batu - Fauziyah, Yenny Zanubah; Arifin, Rois; Normaladewi, Andi (UNIVERSITAS ISLAM MALANG, 2024)
AbstractÂ This study was made to determine the effect of Promotional Strategy, Social Media, through Electronic Word Of Mouth, on the Decision to Visit Educational Tourism Dadaprejo Batu City, the method used in this study is the quantitative method. Sampling in this study used the slovin formula with a total sample of 134 respondents. The data used is primary data through a questionnaire. This study used instrument tests including: validity and reliability tests, normality tests, path analysis tests, t tests, Sobel tests and Coefficient of DeterminationÂ tests.From the results of the research partially obtained results where the Promotion Strategy has a significant effect on the decision to visit, Social Media has a significant effect on the decision to visit, Electronic Word Of Mouth has a significant effect on the decision to visit, Promotion Strategy has a significant effect on the decision to visit through Electronic Word Of Mouth and lastly Social The media has a significant influence on the decision to visit through the Electronic Word Of Mouth.Â Keywords: Promotion Strategy, Social Media, Electronic Word Of Mouth and Visiting Decision